2015
DOI: 10.7196/samjnew.7890
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus genotypes and clinical management of genital warts in women attending a colposcopy clinic in Cape Town, South Africa

Abstract: Background. Genital human papillomavirus (HPV) infection is the most common sexually transmitted viral disease in the world. HPV infection of the genital epithelium is associated with genital warts and malignancies of the lower genital tract. Objectives. To describe the distribution, phenotypic appearance and HPV type associated with genital warts in women.Methods. This was a prospective observational study of all women with genital warts who attended the Colposcopy Clinic, Groote Schuur Hospital, Cape Town, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…11 The reasons for various prevalence rates reported in these studies are unclear; however, it could be because of various methods used for CC screening 20,21,22,23 and sexual practices of women, 7,8,12,24,25 which is explained by higher burden of HPV infection. 26,27,28,29 Despite the effectiveness of highly active retroviral therapy (ART) in preventing the development of cervical lesions, 7,8 interestingly in our study, prevalence of abnormal cervical http://www.phcfm.org Open Access cytology was significantly higher in women with HIV than in women without HIV. Vafaei et al, in their study, reported a greater proportion of women with abnormal cervical cytology amongst HIV-positive women than in the general population.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…11 The reasons for various prevalence rates reported in these studies are unclear; however, it could be because of various methods used for CC screening 20,21,22,23 and sexual practices of women, 7,8,12,24,25 which is explained by higher burden of HPV infection. 26,27,28,29 Despite the effectiveness of highly active retroviral therapy (ART) in preventing the development of cervical lesions, 7,8 interestingly in our study, prevalence of abnormal cervical http://www.phcfm.org Open Access cytology was significantly higher in women with HIV than in women without HIV. Vafaei et al, in their study, reported a greater proportion of women with abnormal cervical cytology amongst HIV-positive women than in the general population.…”
Section: Discussionmentioning
confidence: 61%
“… 11 The reasons for various prevalence rates reported in these studies are unclear; however, it could be because of various methods used for CC screening 20 , 21 , 22 , 23 and sexual practices of women, 7 , 8 , 12 , 24 , 25 which is explained by higher burden of HPV infection. 26 , 27 , 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…This is less than 44% clearance at 3 month follow-up among women (not living with HIV) reported in a study in Cape Town. 30 The long time to AGW clearance among MLHIV supports the idea of introducing quadrivalent HPV vaccines which also prevent AGW. Cost implications of extending the vaccine to boys might generate reluctance by national Ministries of Health.…”
Section: Discussionmentioning
confidence: 93%
“…HIV infection is an important risk factor for HPV infection and persistence. In their Cape Town study, Tayib et al [9] found that almost 80% of patients were HIV-positive. Genital warts are strongly linked to sexual behaviour (in this study the majority of women were sexually active and had had more than one sexual partner), and weakly associated with cigarette smoking (cigarette smoking is biologically associated with decreased antiviral immune cells in the cervical epithelium).…”
Section: Human Papillomavirus Genotypes and Clinical Management Of Gementioning
confidence: 96%